Anatomical-based classification for transoral lateral oropharyngectomy. (December 2019) - De Virgilio, Armando; Kim, Se-Heon; Magnuson, J. Scott; Holsinger, Christopher; Remacle, Marc; Lawson, Georges; Wang, Chen-Chi; Mercante, Giuseppe; Malvezzi, Luca; Iocca, Oreste; Di Maio, Pasquale; Ferreli, Fabio; et al.
Highlights: Aim of the study is proposing a classification of transoral lateral oropharyngectomy procedures. The classification comprises three types of lateral oropharyngectomy. Authors aim is to introduce a simple and easy categorization. Abstract: Purpose: The aim of the study is proposing a classification of different transoral lateral oropharyngectomy procedures in order to ensure better definitions of post-operative results. Methods: The classification resulted from the consensus of the different authors and was based on anatomical-surgical principles. Results: The classification comprises three types of lateral oropharyngectomy: type 1 is the resection of the palatine tonsil deep to the pharyngobasilar fascia; type 2 is performed by removing the entire palatine tonsil, the palatoglossus muscle, the palatopharyngeal muscle and the superior constrictor muscle; type 3 is performed by removing the entire palatine tonsil, the palatoglossus muscle, the palatopharyngeal muscle, the superior constrictor muscle, the buccopharyngeal fascia with extension to the pterygoid muscle and parapharyngeal space fat content. Based on the extension of the dissection we can use the suffix A (soft palate), B (posterior pharyngeal wall), C (base of tongue) and D (retromolar trigone). Conclusion: The proposed classification introduces a simple and easy to use categorization of transoral lateral oropharyngectomies into three classes. Resection extensions are easily described using suffixes.